Rodnostno obnašanje in priseljevanje v Sloveniji v obdobju po drugi svetovni vojni - Josipovič, Damir (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
FERTILITY BEHAVIOUR AND IMMIGRATION IN SLOVENIA IN THE PERIOD FOLLOWING WORLD WAR II. The article presents the history of immigration in Slovenia after the World War II. from the viewpoint of its influence upon the fertility rate of the population. It analyzes immigration into Slovenia, and based upon comparison of different ethnic groups' reproductive level, defines their role in the total fertility behaviour change. The focus is on the comparison of the reproduction rate of immigrant population with that of the majority population. The concluding observation is that immigration has not contributed to the increase of the demographic reproduction rate; contrary to part of the public discourse, it has even been the cause of its decrease.
Keywords: Slovenia; Slovenija; demografski razvoj; rodnost; socialna geografija; human migration; migracije; imigracija; demogeografija